Hereditary nonspherocytic hemolytic anemia caused by glucose-6-phosphate isomerase (GPI) deficiency in a Chinese patient: a case report - Yumei Zu; Hui Wang; Weijia Lin; Chaochun Zou (BMC, 2022)
Abstract Background Glucose phosphate isomerase (GPI) deficiency is a rare autosomal recessive disorder that causes hereditary nonspherocytic hemolytic anemia (HNSHA). Homozygous or compound heterozygous mutation of the GPI gene on chromosome 19q13 is the cause of GPI deficiency. Fifty-seven GPI mutations have been reported at the molecular level. Case presentation A 5-month-old boy was presented with repeated episodes of jaundice after birth. He suffered from moderate hemolytic anemia (hemoglobin levels ranging from 62 to 91 g/L) associated with macrocytosis, reticulocytosis, neutropenia, and hyperbilirubinemia. Whole-exome sequencing showed that he has a missense mutation c.301G > A (p.Val101Met) in exon 4 and a frameshift mutation c.812delG (p.Gly271Glufs*131) in exon 10. Mutation p.Gly271Glufs*131 is a novel frameshift null mutation in GPI deficiency. Conclusion In a patient with recurrent jaundice since birth, mutations in the GPI gene associated with HNSHA should be evaluated. The c.812delG (p.Gly271Glufs*131) variant may be a novel mutation of the GPI gene. Compound heterozygous mutations c.301G > A (p.Val101Met) and c.812delG (p.Gly271Glufs*131) are not relevant to neurological impairment.